Pengaruh Penguasaan Materi Dalam Perkuliahan Microteaching Terhadap Kesiapan Mengikuti Program PPLK Mahasiswa Jurusan Sendratasik FBS UNP - Retna Wati; Darmawati Darmawati (SENDRATASIK UNP, 2022)
This study aims to find out if there is an influence of material mastery on microteaching courses on students' readiness to participate in educational field experience programs PPLK in schools. This type of research is quantitative. The data obtained is processed with statistical formulas. In this study, the subject was Sendratasik students 2017 who had taken Microteaching courses. The research instrument is a questionnaire of readiness in carrying out PPLK and microlearning knowledge test of dance and music. Data collection techniques in the form of questionnaires (questionnaires) and tests (objective questions). Analysis techniques are by collecting data, analyzing data, normality of data and homogeneity of data influence mastery of materials in microteaching lectures to readiness to follow the program of educational field experience PPLK students of Sendratasik FBS UNP Department. The results of the study that the mastery of materials in microteaching lectures contributed 57.31% to the readiness to face the Field Experience Program of Education PPLK Students of Sendratasik FBS UNP department and the rest (42.69%) were influenced by other factors not studied in this study.